The Urgency Of Regulating Elements Of Community Participation In The Toll Road Investment Process In Indonesia - Simon, Simon; Eddy, Triono; Ramlan, Ramlan (Jurnal Cita Hukum, 2025)
The development of toll road infrastructure in Indonesia is one of the national priorities to support economic growth and mobility. However, the success of this project depends not only on government and investor policies, but also on the active participation of the community. Public participation in toll road investment can increase transparency, accountability, and project sustainability. This study aims to examine the urgency of regulating elements of community participation in the toll road investment process in Indonesia. The research method used is normative juridical with an approach to analyzing laws and regulations and case studies. The results of the study show that clearer and more comprehensive public participation arrangements are needed to create an inclusive and sustainable investment environment. The arrangement must include a public consultation mechanism, information transparency, and protection of the rights of affected communities. Thus, community participation not only strengthens the legitimacy of the project, but also contributes to the long-term success of infrastructure development in Indonesia.